Pannexin 2 protein expression is not restricted to the CNS - Le Vasseur, Maxence; Lelowski, Jonathan; Bechberger, John F.; Sin, Wun-Chey; Naus, Christian C. (Frontiers in Cellular Neuroscience, 2014)
Pannexins are proteins homologous to the invertebrate gap junction proteins called innexins and are traditionally described as transmembrane channels connecting the intracellular and extracellular compartments. Three distinct pannexin paralogs (Panx1, Panx2 and Panx3) have been identified in vertebrates but previous reports on pannexin expression and functionality focused primarily on Panx1 and Panx3 proteins. Several gene expression studies reported that Panx2 transcript is largely restricted to the central nervous system (CNS) hence suggesting that Panx2 might serve an important role in the CNS. However, the lack of suitable antibodies prevented the creation of a comprehensive map of Panx2 protein expression and Panx2 protein localization profile is currently mostly inferred from the distribution of its transcript. In this study, we characterized novel commercial monoclonal antibodies and surveyed Panx2 expression and distribution at the mRNA and protein level by real-time qPCR, Western blotting and immunofluorescence. Panx2 protein levels were readily detected in every tissue examined, even when transcriptional analysis predicted very low Panx2 protein expression. Furthermore, our results indicate that Panx2 transcriptional activity is a poor predictor of Panx2 protein abundance and does not correlate with Panx2 protein levels. Despite showing disproportionately high transcript levels, the CNS expressed less Panx2 protein than any other tissues analyzed. Additionally, we showed that Panx2 protein does not localize at the plasma membrane like other gap junction proteins but remains confined within cytoplasmic compartments. Overall, our results demonstrate that the endogenous expression of Panx2 protein is not restricted to the CNS and is more ubiquitous than initially predicted.